Role of Matrix Metalloproteinase 3-mediated α-Synuclein Cleavage in Dopaminergic Cell Death - Choi, Dong-Hee (American Society for Biochemistry and Molecular Biology, 2011)
Evidence suggests that the C-terminal truncation of α-synuclein is equally important as aggregation of α-synuclein in Parkinson disease (PD). Our previous results showed that an endopeptidase, matrix metalloproteinase-3 (MMP3), was induced and activated in dopaminergic (DA) cells upon stress conditions. Here, we report that MMP3 cleaved α-synuclein in vitro and in vivo and that α-synuclein and MMP3 were co-localized in Lewy bodies (LB) in the postmortem brains of PD patients. Incubation of α-synuclein with the catalytic domain of MMP3 (cMMP3) resulted in generation of several peptides, and the peptide profiles of WT α-synuclein (WTsyn) and A53T mutant (A53Tsyn) were different. Combined analysis using mass spectrometry and N-terminal determination revealed that MMP3 generated C-terminally truncated peptides of amino acids 1–78, 1–91, and 1–93 and that A53Tsyn produced significantly higher quantities of these peptides. Similar sizes of peptides were detected in N27 DA cells under oxidative stress and RNA interference to knock down MMP3-attenuated peptide generation. Co-overexpression of cMMP3 with either WTsyn or A53Tsyn led to a reduction in Triton X-100-insoluble aggregates and an increase in protofibril-like small aggregates. In addition, overexpression of the 1–93-amino acid peptide in the substantia nigra led to DA neuronal loss without LB-like aggregate formation. The results strongly indicate that MMP3 digestion of α-synuclein in DA neurons plays a pivotal role in the progression of PD through modulation of α-synuclein in aggregation, LB formation, and neurotoxicity.